2022
DOI: 10.1212/wnl.0000000000201260
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effectiveness and Safety of Rituximab in Neuromyelitis Optica Spectrum Disorder and MOG Antibody Disease

Abstract: Background and Objectives:Rituximab is used widely for relapse prevention in neuromyelitis optica spectrum disorder (NMOSD) and myelin oligodendrocyte glycoprotein (MOG)-IgG associated disease (MOGAD), however data regarding the effectiveness and safety of long-term rituximab use in these conditions are limited. In this study we sought to evaluate long-term clinical outcomes in patients with aquaporin-4 IgG seropositive (AQP4-IgG+) NMOSD and MOGAD treated with rituximab.Methods:We performed a retrospective cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 42 publications
6
33
2
Order By: Relevance
“…Patients with MOGAD treated with rituximab experience relapses and appeared to be less robust than NMOSD despite a complete B-cell depletion. Severe infections and hypogammaglobulinemia occurred in a signi cant proportion of MOGAD patients [30]. In MOGAD, depletion of CD20 T cells by rituximab administration may lead to reduction of protective function, disease relapse and severe infections in patients.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with MOGAD treated with rituximab experience relapses and appeared to be less robust than NMOSD despite a complete B-cell depletion. Severe infections and hypogammaglobulinemia occurred in a signi cant proportion of MOGAD patients [30]. In MOGAD, depletion of CD20 T cells by rituximab administration may lead to reduction of protective function, disease relapse and severe infections in patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 Patients with MOG-IgG are frequently responsive to corticosteroids in the acute phase and less responsive to rituximab as maintenance therapy, whereas those with AQP4-IgG usually require second-line acute treatments such as plasma exchange and respond quite well to rituximab in the long term. 10 All these differences led to the recognition of MOGAD as a separate entity, culminating in the International MOGAD Panel proposed criteria in 2023. 8 Of note, unlike in MS or NMOSD, the positivity of a biomarker (MOG-IgG) is indispensable for the fulfillment of the diagnostic criteria, making this a good example of the precision medicine approach.…”
Section: Mogadmentioning
confidence: 99%
“…9 Patients with MOG-IgG are frequently responsive to corticosteroids in the acute phase and less responsive to rituximab as maintenance therapy, whereas those with AQP4-IgG usually require second-line acute treatments such as plasma exchange and respond quite well to rituximab in the long term. 10…”
Section: Redefining Disease Classificationmentioning
confidence: 99%
“…Open-label studies suggest that several therapies reduce the risk of relapse in patients with NMOSD. For example, the efficacy of rituximab in reducing the annual relapse rate (ARR) has been reported in multiple studies [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Metaanalyses of such studies found that, collectively, ≈ 60% of patients were relapse-free on rituximab [24].…”
Section: Introductionmentioning
confidence: 99%
“…Metaanalyses of such studies found that, collectively, ≈ 60% of patients were relapse-free on rituximab [24]. Serious adverse events such as serious or severe infection or infusion reaction occurred in 26% of patients, raising concerns regarding rituximab as first-line therapy [23,25]. Importantly, the majority of these studies did not use the 2015 International Panel for NMOSD Diagnosis (IPND) criteria for inclusion.…”
Section: Introductionmentioning
confidence: 99%